Microstructure and Tensile Properties of Fine-Grained Bulk Copper Fabricated by Thermomechanical Consolidation of Copper Nanopowder/Micron-Sized Powder Blend - Bhatta,Gyanendra (2022)
Abstract Samples of fine structured Cu were fabricated by spark plasma sintering (SPS) of compacts of Cu nanopowder/micron-sized powder blend with a ratio of 3:7 by weight, and one of the SPSed samples was further processed by hot extrusion. The microstructures of the as-SPSed and the as-extruded samples and the tensile properties and fracture behavior of the as-extruded sample were studied. It was found that the microstructures of the samples consist of a concoction of ultrafine and coarse grains with high dislocation densities ( ~1015 m-2) as a result of microstructural evolution during material processing. Some nanograins were oxidized to form Cu2O particles residing around the coarse grains. Extrusion of the SPSed sample increases its microhardness from 70 HV to 90 HV. The electrical conductivity of the as-extruded sample reaches 87% international annealed copper standard (IACS), and its tensile properties are 200 MPa for yield strength, 218 MPa for ultimate tensile strength and 9% for elongation to fracture. The tensile test specimens from the as-extruded sample exhibit nearly ideal plastic deformation and undergo ductile fracture, suggesting that the fine-grained copper is a highly desirable material for high strength electrical conductors.